2021
DOI: 10.4018/978-1-7998-7331-0.ch010
|View full text |Cite
|
Sign up to set email alerts
|

Employer Perspectives on Virtual International Working

Abstract: This chapter summarises the key findings from a doctoral research project that examined employer perceptions of virtual, international working immediately before, during, and after the global pandemic took hold in Spring 2020. The purposive interview sample included new and experienced professionals who work in communication related roles within public, private, and third sector organisations. The research builds on previous evaluative research concerning student and faculty perceptions of virtual exchange. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Research conducted on students engaging in GVT projects has found that GVT projects are conducive to developing students' skills in digital communication, virtual project management skills and intercultural competence, thus preparing them for the global work environment (Crawford, 2021;Swartz, et al, 2021;Hackett, et al, 2023). This study's qualitative responses further substantiate these findings.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Research conducted on students engaging in GVT projects has found that GVT projects are conducive to developing students' skills in digital communication, virtual project management skills and intercultural competence, thus preparing them for the global work environment (Crawford, 2021;Swartz, et al, 2021;Hackett, et al, 2023). This study's qualitative responses further substantiate these findings.…”
Section: Discussionsupporting
confidence: 61%
“…In the post COVID-19 pandemic era, the focus for higher education has turned to imparting skills and abilities conducive to remote work. The skills fundamental for post-pandemic employment include digital fluency, virtual project management skills, as well as intercultural communication competence (Crawford, 2021;Elliot, 2021;Engler, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Izzy Crawford [8, Skills that are generally considered irrelevant to a particular task, subject, or field of study, however, have a wide The importance of transversal skills in higher education curricula and in the labor market range of applications in a variety of contexts and settings. The student's ability to interpret information and process it using competencies acquired in other areas Roberto Pierdicca, Emanuele Frontoni, Maria Paola Puggioni, Eva Savina Malinverni, Marina Paolanti [10, Source: [11].…”
Section: Table 1 Content Analysis Of the Definition Of "Transversal S...mentioning
confidence: 99%
“…Through participating in this project during a pandemic, students acquired soft skills that helped them to navigate some of the challenges they faced due to the pandemic; they developed emotional connections with help of technology and cultivated global camaraderie and empathy (Ritter et al., 2018 ). The experience also highlighted the value of global learning and emphasized the importance of incorporating educational technologies and methods that are adaptable and reflect the needs of the modern workplace (see eg, Crawford, 2021 ).…”
Section: Implications For Future Teaching and Learningmentioning
confidence: 99%